The Urgency of Handling Illegal, Unreported and Unregulated Fishing in the Indonesian Border Region Perspective: Marine Security in the Makassar Strait - Hasan, Yulia; Nurbaiti, Siti; Hamid, Abd. Haris (Padjadjaran Journal of International Law, 2024)
ASEAN Outlook on Indo-Pacific (AOIP) plays a role in maintaining peace, security, stability and prosperity in the Asia Pacific and Indian Ocean (Indo-Pacific) region. However, due to common and competing interests, there are still conflicts in the region's implementation. Maritime security cooperation, which includes addressing illegal, unreported, and unregulated (IUU) fishing, is one of the most important issues in the ASEAN region. The research intends to examine law enforcement against IUU violations in the ASEAN region, as well as the consequences of IUU violations by ASEAN countries on waters in the Makassar Strait. This is a qualitative study that employs a normative-empirical approach. The first problem is analyzed using the normative aspect, which is based on international and national law on ASEAN agreements on IUU, law enforcement, and other issues. While the empirical aspect is used to analyze the second problem through in-depth interviews about Makassar Strait water supervision and law enforcement. Based on the research findings, IUU law enforcement in the ASEAN Region must be carried out firmly to parties that threaten security and stability in the ASEAN Region, as outlined in each agreement participant's national law. Meanwhile, the legal consequences of IUU violations in the ASEAN Region have an impact on the security and stability of the waters of the Makassar Strait.